(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: The establishment of credit policy is an integral part of the entire decision-making process on the manner and structure of corporate financing. Determining the credit policy is crucial for adequate management of a company’s net working capital and its financing, in order to support continuous operation and the earning capacity of the company. In this process, the company will be influenced by the market in which it operates and by many others external and internal factors. For example, companies operating in less developed financial markets will find it more difficult to obtain the necessary financing. Such companies are most dependent on short-term financing in general, and trade credit in particular. This paper analyzes primarily internal factors - trade receivables and payables. Accordingly, the main goal of this paper is to investigate the relationship between the profitability of SMEs in the Republic of Croatia and their use of trade credit. Methodology: In order to achieve the main goal and prove the hypotheses, panel data analysis examined the impact of trade credit on the level of profitability of Croatian SMEs. Results: The results show that delaying payments to suppliers increased the profitability of the company. Furthermore, the results show that a decrease in receivables did not increase the profitability of SMEs. Conclusion: Croatian SMEs can increase the profitability by not delaying the payment of obligations to suppliers for too long.